Analysis of Employee Needs in District Government Environment of Sidoarjo District: “Case Study of Balongbendo District, Sidoarjo District, and Tulangan District" - Yossyefa Nabila Choirunnisa Putri; Singgih Manggalou (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract The study entitled Analysis of Employee Needs in Sub-districts in Sidoarjo Regency Government: "Case Study of Balongbendo, Sidoarjo, and Tulangan" aims to identify the needs and availability of civil servants in the three sub-districts. Using descriptive qualitative methods, data were collected through interviews, observations, and documentation. The results showed that the job descriptions for each division in the three sub-districts were well defined. Sidoarjo in particular faced a significant shortage of staff, filling only half of the positions needed. Balongbendo had several important roles unfilled, while Tulangan was better off, with almost full staff but facing challenges in data processing roles. Keywords: Employee Needs, Job Map, Employee Supply.